Legal Literature Review of Peer to Peer Lending in Indonesia: Building Sharia FinTech Ecosystem: Literatur Hukum Peer to Peer Lending di Indonesia: Membangun Ekosistem FinTech Syariah - Arini, Annisa Dian (Sharia and Law Faculty of Sunan Kalijaga Islamic State University Yogyakarta, 2024)
Abstract: This article investigates the extent to which peer-to-peer (P2P) lending regulations in Indonesia, both in the context of formal law and Islamic law, have been effective in supporting economic growth. Employing a normative juridical approach, the article highlights various regulations introduced by the government to enhance transparency and accountability in the implementation of fintech P2P lending in Indonesia. Although measures such as the imposition of daily interest rate limits have been implemented to protect consumers, concerns remain regarding the effectiveness of supervision, particularly in safeguarding vulnerable consumers. The study also underscores the importance of financial and digital literacy in helping both borrowers and lenders understand the risks and benefits of P2P lending. Key challenges in integrating Sharia law principles, including the prohibitions on ribā (usury) and gharar (uncertainty), have the potential to constrain financial innovation and reduce competitive lending options. The findings suggest the need for a more flexible regulatory approach and closer collaboration between regulators, the industry, and religious authorities to ensure compliance with Sharia law while supporting the growth of the sector. Continuous education for users is also essential to enhance protection and financial inclusion within the Sharia-compliant P2P lending ecosystem in Indonesia. Abstrak: Artikel ini meneliti sejauh mana regulasi peer-to-peer (P2P) lending di Indonesia, baik dalam konteks hukum formal maupun hukum Islam, telah berfungsi dengan baik dan mendukung bergeraknya roda perekonomian. Menggunakan pendekatan yuridis normatif, artikel ini menyoroti berbagai regulasi yang ditetapkan oleh Pemerintah dalam meningkatkan transparansi dan akuntabilitas pada penyelenggaraan fintech P2P di Indonesia. Meskipun langkah-langkah seperti pembatasan suku bunga harian telah diberlakukan untuk melindungi konsumen, terdapat kekhawatiran terkait efektivitas pengawasan, terutama dalam melindungi konsumen yang rentan. Penelitian ini juga menekankan pentingnya literasi keuangan dan digital untuk membantu para peminjam dan pemberi pinjaman memahami risiko dan manfaat dari pinjaman P2P. Tantangan utama dalam mengintegrasikan prinsip-prinsip hukum Syariah, termasuk larangan ribā dan garar, berpotensi membatasi inovasi keuangan dan mengurangi opsi pinjaman yang kompetitif. Temuan dalam penelitian ini menyarankan perlunya pendekatan regulasi yang lebih fleksibel serta kolaborasi yang lebih erat antara regulator, industri, dan otoritas keagamaan untuk memastikan kepatuhan terhadap hukum Syariah sekaligus mendukung pertumbuhan sektor ini. Edukasi berkelanjutan bagi pengguna juga diperlukan guna meningkatkan perlindungan dan inklusi keuangan dalam ekosistem P2P lending syariah di Indonesia.